Fabrication of A Mushroom Planting Media Mixing Machine For Mushroom Farmers in Desa Gondowangi, Kecamatan Wagir, Kabupaten Malang - Kris Witono; Nurhadi Nurhadi; Eko Yudiyanto; Talifatim Machfuroh; Satworo Adiwidodo; Rilis Eka Perkasa (Journal of Community Engagement, 2025)
White oyster mushrooms (Pleurotus ostreatus) represent a vital agricultural commodity and a major source of income for residents of Dusun Wiloso, Desa Gondowangi, Kecamatan Wagir, Kabupaten Malang. Despite their economic potential, the productivity of local mushroom farmers remains constrained by the conventional manual process of preparing baglog planting media, which involves mixing wood sawdust and rice bran. This traditional method is not only labor-intensive and time-consuming but also prone to inconsistencies that may damage the planting media and reduce overall yields. In response to these challenges, the Community Service Program (PPM) introduced an innovative training and technology transfer initiative focused on the design, fabrication, and utilization of a mushroom planting media mixing machine. This intervention effectively mechanizes the mixing process, thereby improving production efficiency, ensuring greater uniformity and quality of the planting media, and enhancing cultivation outcomes. Beyond its technical advantages, the program promotes local capacity building by expanding community knowledge in mechanical engineering and fabrication, fostering innovation, and stimulating entrepreneurial opportunities among local fabrication workshops. These workshops play a strategic role in sustaining the availability of appropriate agricultural technologies, supporting the continuous improvement of mushroom cultivation systems, and strengthening the region’s technological independence. Consequently, this PPM initiative not only addresses critical production bottlenecks but also contributes to broader goals of rural economic development, technological empowerment, and sustainable community self-reliance within Dusun Wiloso.